2015
DOI: 10.3389/fmicb.2015.00801
|View full text |Cite
|
Sign up to set email alerts
|

Chronic widespread dermatophytosis due to Trichophyton rubrum: a syndrome associated with a Trichophyton-specific functional defect of phagocytes

Abstract: Dermatophytes are agents of typically benign superficial infections. However, an increasing number of severe infections in immunocompromised hosts has been reported. We aimed to understand the factors underlying the existence of a cohort of patients presenting with chronic widespread dermatophytosis (CWD) due to Trichophyton rubrum, but with no signs of immunodeficiency. Their disease is usually recurrent and difficult to manage. Fourteen patients meeting the following criteria for CWD were studied: T. rubrum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
30
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 42 publications
(53 reference statements)
0
30
0
1
Order By: Relevance
“…[ 5 ] The dermatophytic clearance from the skin is secondary to the activation of cell-mediated immunity (CMI) and is Th1/Th17-dependent. [ 6 ] It is of interest to note that acute dermatophytosis is associated with Th1 response, whereas in cases of chronic dermatophytosis, the immunity is skewed toward Th2 cytokines with high levels of IgE and IgG4 antibodies. [ 5 ] One could propose that individuals with defective tilt of immunity toward Th2 cytokines would be more predisposed to chronic dermatophytic infection.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[ 5 ] The dermatophytic clearance from the skin is secondary to the activation of cell-mediated immunity (CMI) and is Th1/Th17-dependent. [ 6 ] It is of interest to note that acute dermatophytosis is associated with Th1 response, whereas in cases of chronic dermatophytosis, the immunity is skewed toward Th2 cytokines with high levels of IgE and IgG4 antibodies. [ 5 ] One could propose that individuals with defective tilt of immunity toward Th2 cytokines would be more predisposed to chronic dermatophytic infection.…”
mentioning
confidence: 99%
“…In patients who suffer from chronic dermatophytosis, defective phagocytosis of the fungal hyphae is observed. [ 6 ] Mannans produced by T. rubrum work by inhibiting the critical steps in antigen processing and presentation. [ 4 ] The free radicals and nitric oxide release have been found to be 20–30% lower than that of controls in patients of chronic dermatophytosis, indicating a defective killing mechanism as well.…”
mentioning
confidence: 99%
“…Dermatophytes are keratinophilic fungi involved in superficial mycoses, whose incidence has increased in recent years, particularly chronic and recurrent forms, with Trichophyton rubrum as the most common species in human cases . Studies conducted over the past few years have reported an increase in resistance to antifungal agents commonly used to treat cutaneous mycoses, including dermatophytosis .…”
Section: Introductionmentioning
confidence: 99%
“…Some features, including the ability to form biofilms, may be associated with dermatophyte unresponsiveness to antifungals . In general, biofilms are commonly implicated in the antifungal tolerance of microorganisms, commonly requiring high minimum inhibitory concentration (MIC) values to inhibit their growth …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation